2019
DOI: 10.1016/j.seppur.2019.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Cd2+ removal from aqueous solution by multifunctional mesoporous silica: Equilibrium isotherms and kinetics study

Abstract: In this work, a novel amino-functionalized mesoporous microsphere was synthesized to remove cadmium ions from water. The Fe 3 O 4 @SiO 2 @m-SiO 2 -NH 2 micro-spheres were successfully prepared via a facile two-stage process by coating of the as-synthesized magnetic cores with a silica shell followed by increasing the porosity of the structure using a cationic surfactant as structure-directing agents. The template removal from the structure has been performed following the method of solvent extraction and metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…The Langmuir model fits relatively well the adsorption data for Fe 3 O 4 NPs, which suggests that the assumption of a monolayer deposition might be correct for this adsorbent (Figure 6a). The q m value of Fe 3 O 4 NPs @APTES is 1334.94 mg/g, which is reasonable compared with others reported previously by Javaheri, F. et al [46] of 884.906 mg/g for Fe 3 O 4 @SiO 2 @m-SiO 2 -NH 2 and 769.2 mg/g for nano zerovalent iron presented by Boparai et al [47]. The Freundlich linear model is not restricted to a monolayer formation and includes the heterogeneous interaction between the material surface and the metal ion.…”
Section: Adsorption Isothermssupporting
confidence: 91%
“…The Langmuir model fits relatively well the adsorption data for Fe 3 O 4 NPs, which suggests that the assumption of a monolayer deposition might be correct for this adsorbent (Figure 6a). The q m value of Fe 3 O 4 NPs @APTES is 1334.94 mg/g, which is reasonable compared with others reported previously by Javaheri, F. et al [46] of 884.906 mg/g for Fe 3 O 4 @SiO 2 @m-SiO 2 -NH 2 and 769.2 mg/g for nano zerovalent iron presented by Boparai et al [47]. The Freundlich linear model is not restricted to a monolayer formation and includes the heterogeneous interaction between the material surface and the metal ion.…”
Section: Adsorption Isothermssupporting
confidence: 91%
“…It was clear that Cd 2+ removal using tobermorite was well described with the Langmuir model (R 2 = 0.8983), which suggested that Cd 2+ removal was a process of monolayer chemical adsorption that probably occurred through surface complexation with tobermorite [ 2 , 39 ]. Different studies also showed that Cd 2+ removal with a range of other adsorbents was fitted better with the Langmuir model than with the Freundlich model [ 35 , 40 , 41 ]. In addition, Q m , as the maximum adsorption capacity calculated from the Langmuir model, could be used as the theoretical saturated adsorption capacity.…”
Section: Resultsmentioning
confidence: 99%
“…The continuous increase in the levels of toxic heavy metal ions in major water supplies and freshwater resources as a result of extensive metallurgical, industrial, and mining activities represents critical challenges for the safe future of humanity [1,2]. Such metals have high accumulation and toxicity behavior, which classifies them as hazardous pollutants for humans, animals, and aquatic organisms [3,4]. Dissolved arsenic ions (As) have been recognized as highly toxic forms of water contaminants [5,6].…”
Section: Introductionmentioning
confidence: 99%